"Bordering on Treason"? Sir Raphael Cilento and Pre‐Second World War Fascism in Australia. (1st May 2019) - Deery, Phillip; Kimber, Julie
Abstract : Sir Raphael Cilento died on 16 April 1985 at the age of ninety‐two. The notice in the Canberra Times spoke of Cilento's "worldwide" reputation in tropical medicine, his contribution to the public health service in Queensland, and his role with the United Nations in the immediate post‐war years. In short, he was an "eminent son of Australia". But Sir Raphael Cilento's halo has been tarnished by his persistent eugenicist beliefs and his later association with the anti‐Semitic League of Rights. There were also lingering allegations and rumours about his apparent pre‐war association with Fascism. Without the evidentiary "smoking gun", this association has occasionally been alluded to by scholars but never fully examined. Drawing on an unreleased, previously classified security file, this article addresses this question in Cilento's life. Through an examination of what the security service and military intelligence knew of Cilento's activities, the article argues that Cilento was at best an active fellow traveller and at worst a card‐carrying Fascist who narrowly escaped internment.